2017
DOI: 10.1002/ldr.2769
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the North–South Capital Flows or Rise of South–South Land Deals? Features of Land Acquisition in Ethiopia

Abstract: Transnational land deals are among the most contested but inadequately understood topics. In this paper, we focus on the features of large‐scale transnational land deals (LSTLDs) in the Global South through an examination of Ethiopia. We apply a mixed method (qualitative and quantitative) research design.Results indicate that in 2005–2015, the government leased nearly 2·47 million ha of the country's approximate total 114 million ha area and offered 11·5 million ha of cultivable land to domestic and transnatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…These findings have been confirmed in previous studies and are consistent with the research idea of this paper [9,11,13,65]. Relying on previous research results [21,66], the above theoretical analysis and the empirical results, we find that, in fact, for western China, there is not a simple one-way relationship between farmland transfer and rural financial development, but a two-way relationship [8,13,21]. Similarly, our results further support this research view.…”
Section: Contrast To Prior Studiessupporting
confidence: 94%
“…These findings have been confirmed in previous studies and are consistent with the research idea of this paper [9,11,13,65]. Relying on previous research results [21,66], the above theoretical analysis and the empirical results, we find that, in fact, for western China, there is not a simple one-way relationship between farmland transfer and rural financial development, but a two-way relationship [8,13,21]. Similarly, our results further support this research view.…”
Section: Contrast To Prior Studiessupporting
confidence: 94%
“…If business growth is to improve the livelihood of the many through production support, employment, market uptake and market outlets for smallholders, then it should look beyond the bottom line and incorporate social objectives of inclusion and sustainability in its business models (Deininger, 2011; European Union, 2013; West & Haug, 2017). Responsible investments that consider the impact on the local population and environment at the very least pursue a ‘do no harm’ principle in their operations (Cotula et al, 2009; Teklemariam et al, 2017). Also, public support to the private sector is often made conditional on ‘doing good', that is, including positive societal impact in the objectives of the business model.…”
Section: From Private Sector Engagement To Inclusive Businessmentioning
confidence: 99%
“…Yet, the lack of research on these actors has made them largely invisible. Only two studies in the Web of Science results included diaspora investors in their data collection [36,37]-the latter of which showed that diaspora investors hired nearly twice as many permanent employees when compared to foreign investors. Even if only in passing, only nine papers (20%) mentioned diaspora at all.…”
Section: What Are We Missing?mentioning
confidence: 99%